Resolution of the Islamic Academy of Fikh on Transplantation of Human Organs and Embryos - Javadly, Gamar Khanum (Scholarya Demo Journal of Ruby, 2020)
The formation and development of bioethics is closely connected with the transformation of traditional ethics in general and medical ethics separately. The interest in bioethics is primarily due to the special attention of the public to human rights, the testing of new technologies and medical devices over people, which, in turn, have created many problems that require solving legal and spiritual regulation. Transplantation of organs and cells is carried out in order to save a human life or restore the patient’s viability by replacing organs and stem cells extracted from living or dead people. Before adopting the relevant resolution, the Fiqh Islamic Academy conducted investigations on the transplantation of human organs and embryos, which are aimed at saving lives and at the same time cause serious disagreements among Muslim scholars. The main problem is the feasibility of using a live or dead donor. Disagreements around transplantation are known to the world from the beginning of the 2nd century BC, but to this day, they have not lost their relevance. There is still fierce debate around this topic and there are no concrete solutions. According to Muslim scholars, the reason for the debate is the postulates derived from the original sources of Islam, such as human dignity, the value of life, the body the repository of the soul and the fact that a person is not the sovereign owner of either his fate or his body. The classification of these assumptions leads to two main points the ownership (property) and the dignity (superiority) of human life.